Lung-specific interleukin 6 mediated transglutaminase 2 activation and cardiopulmonary fibrogenesis - Penumatsa, Krishna C.; Sharma, Yamini; Warburton, Rod R.; Singhal, Adit; Toksoz, Deniz; Bhedi, Chinmayee D.; Qi, Guanming; Preston, Ioana R.; Anderlind, Christina; Hill, Nicholas S.; Fanburg, Barry L. (Frontiers in Immunology, 2024)
Pulmonary hypertension (PH) pathogenesis is driven by inflammatory and metabolic derangements as well as glycolytic reprogramming. Induction of both interleukin 6 (IL6) and transglutaminase 2 (TG2) expression participates in human and experimental cardiovascular diseases. However, little is known about the role of TG2 in these pathologic processes. The current study aimed to investigate the molecular interactions between TG2 and IL6 in mediation of tissue remodeling in PH. A lung-specific IL6 overexpressing transgenic mouse strain showed elevated right ventricular (RV) systolic pressure as well as increased wet and dry tissue weights and tissue fibrosis in both lungs and RVs compared to age-matched wild-type littermates. In addition, IL6 overexpression induced the glycolytic and fibrogenic markers, hypoxia-inducible factor 1α, pyruvate kinase M2 (PKM2), and TG2. Consistent with these findings, IL6 induced the expression of both glycolytic and pro-fibrogenic markers in cultured lung fibroblasts. IL6 also induced TG2 activation and the accumulation of TG2 in the extracellular matrix.Pharmacologic inhibition of the glycolytic enzyme, PKM2 significantly attenuated IL6induced TG2 activity and fibrogenesis. Thus, we conclude that IL6-induced TG2 activity and cardiopulmonary remodeling associated with tissue fibrosis are under regulatory control of the glycolytic enzyme, PKM2.